Analysis of Liver Function Test in Common Bile Duct Stone: A Descriptive Cross sectional study - Pun, Ashis; Dhungana, Amit; Shrestha, Ronit Kumar; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2023)
Introduction: Liver function test (LFT) is a useful tool to differentiate between the obstructive and hepatocellular cause for biliary obstruction. Therefore this study was done to see the accuracy of LFT in predicting common bile duct (CBD) stones. Methods: A descriptive cross sectional study was carried out on patient undergoing endoscopic retrograde cholangiopancreatography for CBD stones at Bharatpur Hospital and Dev Hospital from 2021 June 15 to 2022 October 15. Ethical clearance was taken from Institutional Review Committee Bharatpur Hospital reference number 079/80-013. The convenient sampling method was applied. Data were collected and analyzed in statistical package for the social sciences version 22. Results: Out of 95 patients higher aged female predominance was seen. The overall incidence of abnormal LFT in CBD stones was 85.3%. All the parameters of LFT were raised in majority of the cases of CBD stones and among these, SGOT was mostly increased (75.6%). In patients with ERCP findings of sludge in bile duct have increased total, direct and indirect bilirubin than in patient with CBD stone and this finding was found to be statistically significant. However, other liver parameters were comparable.Similarly, total, direct and indirect bilirubin, serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT) and alkaline phosphatase (ALP) were equally raised with both group of CBD stones with and without cholecystitis. Conclusion: Liver function test was equally raised in both case of CBD stone with and without cholecystitis. Although ALP and total bilirubin represented the most reliable predictors in obstructive jaundice, SGOT might also be added tool to exclude choledocholithiasis.